Adamantanes might be protective from COVID-19 in patients with neurological diseases: multiple sclerosis, parkinsonism and cognitive impairment - Rejdak, Konrad; Grieb, Paweł (Multiple sclerosis and related disorders, 2020)
•We report on a questionnaire-based study performed to assess severity of COVID-19 in patients suffering from multiple sclerosis, Parkinson's disease and cognitive impairment.•All patients were receiving treatments with either amantadine or memantine on stable registered doses.•In all patients infection with SARS-CoV-2 was confirmed by rtPCR but none of them developed clinical manifestations of infectious disease. They also did not report any significant changes in neurological status in the course of primary nervous system disease. Facing the outbreak of coronavirus disease 2019 (COVID-19) pandemic, there is an urgent need to find protective or curable drugs to prevent or to stop the course of the coronavirus SARS-CoV-2 infection. Recent evidence accumulates that adamantanes, widely used in different neurological diseases, could be repurposed for COVID-19. We hereby report on a questionnaire-based study performed to assess severity of COVID-19 in patients suffering from multiple sclerosis (n=10), Parkinson's disease (n=5) or cognitive impairment (n=7). In all patients infection with SARS-CoV-2 was confirmed by rtPCR of nasopharyngeal swabs. They were receiving treatment with either amantadine (n=15) or memantine (n=7) in stable registered doses. All of them had two-week quarantine since documented exposure and none of them developed clinical manifestations of infectious disease. They also did not report any significant changes in neurological status in the course of primary nervous system disease. Above results warrant further studies on protective effects of adamantanes against COVID-19 manifestation, especially in subjects suffering from neurological disease.